Describing capability, opportunity, and motivation for food safety practices among actors in the Cambodian informal vegetable market - Mosimann, Sabrina; Ouk, Keorimy; Bello, Nora M.; Chhoeun, Malyheng; Vipham, Jessie; Hok, Lyda; Ebner, Paul (Frontiers in Sustainable Food Systems, 2023)
Several Cambodian initiatives seek to improve nutritional outcomes via increased production and consumption of nutrient-dense foods, including vegetables. However, food safety gaps in informal markets, where most vegetables are purchased, allow for the transmission and persistence of foodborne pathogens and threaten the positive nutritional outcomes associated with vegetable consumption. This study sought to describe the perceptions of Cambodians involved with informal vegetable markets regarding their capabilities, opportunities, and motivations to implement food safety practices in order to inform food safety engagement programs that address these gaps. This research further aimed to develop a quantitative tool that could be used to assess capability, opportunity, and motivation in a wide range of development contexts. To these ends, a questionnaire assessing these perceptions was developed using the Capability, Opportunity, Motivation-Behavior [COM-B] model of behavior and the Theoretical Domains Framework. The questionnaire was piloted with vegetable vendors in Phnom Penh (n = 55), revised, and subsequently implemented in the provinces of Battambang and Siem Reap with vegetable producers, distributors, and vendors (n = 181). Confirmatory factor analysis resulted in a nine-factor model based on the questionnaire’s nine constructs with a comparative fit index of 0.91, a Tucker-Lewis index of 0.89, and a root mean square error of approximation of 0.05. Further analysis indicated that vegetable vendors and distributors had significantly higher (P < 0.05) levels of perceived motivation and capability to implement the target food safety practice compared to their perceived opportunity to do so. Among farmers, however, levels of perceived motivation were significantly higher (P < 0.05) than levels of perceived opportunity and capability. In addition, vendors in Battambang had significantly higher (P < 0.05) levels of perceived capability, opportunity, and motivation to implement the target food safety practice in comparison to farmers in either province. Vendors in Battambang had significantly higher (P < 0.05) levels of perceived opportunity and motivation than vendors in Siem Reap. These data suggest that efforts to bolster vegetable vendors’ and distributors’ perceived opportunity and vegetable farmers’ perceived opportunity and capability to implement food safety practices could increase the likelihood of adoption of the target food safety practice.